Midwives' experiences of reducing maternal morbidity and mortality from postpartum haemorrhage (PPH) in Eastern Nigeria - Felicity Agwu Kalu; Joan N. Chukwurah (BMC, 2022)
Abstract Background Postpartum haemorrhage (PPH) is one of the major complications of childbirth which may result in maternal morbidity and mortality, especially in low and middle-income countries like Nigeria. Midwives play a vital role in preventing and managing PPH in Nigerian rural communities. The aim of this study is to understand the experiences of midwives in rural maternity care settings in order to provide appropriate support and improve practice. Methods An exploratory, qualitative study of a purposive sample of 15 practicing midwives was carried out using semi-structured interviews from November 2018 to February 2019. Data were transcribed verbatim and analyzed using content analysis. Results Four themes were identified: 1. interventions for preventing PPH; 2. approaches to managing PPH; 3. challenges of preventing and managing PPH and 4. ways of supporting midwives to overcome these challenges in rural health care settings. Midwives employed various strategies, such as antenatal education, diagnosis and treatment of anaemia to counteract complications from possible PPH. Understanding PPH as a life-threatening condition enabled the midwives to provide holistic and effective management that sometimes involved a multidisciplinary team approach. Inadequate resources and delay in seeking health care, however, militate against their efforts. The midwives also identified the need for continuing education and training to enhance their standards of care. Conclusion These midwives in Nigerian rural health care settings engage in preventive practices and active management of PPH though not without barriers, such as inadequate resources. There is a need for midwives in rural areas to have cultural competence, be provided with adequate resources and participate in ongoing education in order to be more effective.